COGNITIVE DEVELOPMENT FEATURES OF STUDENTS IN A DIGITAL LEARNING ENVIRONMENT. (Universal International Scientific Journal, 2026)
This article analyzes the pedagogical possibilities of teaching inclusive education in a digital educational environment from a scientific, theoretical and practical point of view. It also substantiates that the processes of digital transformation create the need for new didactic approaches, interactive methods and the formation of individual educational trajectories in the education system. The effectiveness of using digital platforms, distance learning technologies, multimedia tools and adaptive learning systems in the process of teaching inclusive education is highlighted.
Keywords: inclusive education, adaptive learning, differentiated approach, distance learning, individual learning trajectory, multimedia tools.